THE EFFECT OF WOMEN COMMISSIONERS ON FIRMS' VALUE IN THE INDONESIAN MANUFACTURING INDUSTRY: MEDIATING ROLE OF ENVIRONMENTAL ENGAGEMENT - Annisa Ayu Putri Sutarsa; Bambang Tjahjadi (Assets: Jurnal Akuntansi dan Pendidikan, 2023)
ABSTRACTIssues regarding gender equality have been increasing since the United Nations made it one of the global goals in the Sustainable Development Goals. It has put a question of whether the role of women will have a good impact on the company. In this study, female commissioners in 129 Indonesian manufacturing companies will be examined concerning their roles from 2015 to 2019. WarpPLS7.0 software was used to analyze the data using structural equation modeling - partial least squares (SEM-PLS). This study discovered that the association between women on commissions and firms' values is mediated by environmental engagement. Furthermore, this study also found significant influences between Women on Commissioners and Firms' Values. The results of this study are expected to contribute significantly to the development of the literature and can practically be considered by the company's stakeholders.ABSTRAKIsu – isu mengenai kesetaraan gender semakin meningkat sejak United Nation menjadikannya sebagai salah satu global goals dalam Sustainable Development Goals. Hal ini memunculkan pertanyaan apakah peran perempuan akan memberikan dampak yang baik di perusahaan. Penelitian ini bertujuan untuk menyelidiki peran komisioner wanita dalam perusahaan – perusahaan di Indonesia. Dengan melibatkan 129 perusahaan manufaktur dalam rentang waktu 2015 – 2019 dan terdaftar dalam Bursa Efek Indonesia (BEI). Data yang diperoleh dianalisis menggunakan structural equation modelling – partial least square (SEM-PLS) dengan software WarpPLS7.0. Dari pengujian tersebut, didapat bahwa Environmental Engagement memediasi hubungan Women on Commissioner terhadap Firms’ Value. Selain itu, penelitian ini juga membuktikan bahwa adanya pengaruh signifikan pada hubungan women on commissioner terhadap firms’ value. Hasil dari penelitian ini diharapkan berkontribusi besar pada pengembangan literatur serta secara praktis dapat menjadi bahan pertimbangan para pemangku kepentingan perusahaan.